Choices Regarding Thrombolysis Are Modified by the Way to Transfer the Messages - Gong, Jingjing; Zhang, Yan; Gao, Hongyan; Wei, Wei; Lv, Jing; Liu, Hongyun; Huang, Yonghua (Frontiers in Neurology, 2017)
Although thrombolysis is the most effective medical treatment for acute ischemic stroke, many stroke patients eligible for thrombolysis miss this treatment as a result of delay or refusal by the patients and/or their proxies. To explore the influences of prognostic information for different intervals from stroke onset to the start of thrombolytic treatment (OTT) and other factors on the preferences of patients/proxies regarding thrombolytic therapy, a cross-sectional, discrete-choice experiment was performed between August 2013 and September 2014. A total of 613 Chinese inpatients or their immediate family members were consecutively recruited at the Department of Neurology. After random assignment to a negative-framing group or a positive-framing group, the subjects completed a series of surveys, including 9 items about thrombolysis. Latent class analysis (LCA) was used to examine participants’ preference paradigms for thrombolysis and to categorize the participants into different subgroups. Subsequently, regression analyses were conducted to explore predictors of categorization of the participants into each subgroup and to construct a thrombolytic decision-making model. LCA revealed an optimal 3-subgroup model including a Consent to thrombolysis subgroup and Objection to thrombolysis subgroups 1 and 2. Multiple regression analysis demonstrated that compared with assignment to the Consent to thrombolysis subgroup, assignment to Objection to thrombolysis subgroup 1 or 2 could be predicted by different factors. 2 tests indicated effects of framing and other factors on participants’ choices regarding thrombolysis. Choices regarding thrombolysis were modified by not only prognostic information for different OTT intervals but also message framing, presentation format, and socio-demographic characteristics. To facilitate consent to thrombolysis, physicians should convey prognostic information to patients/proxies on the basis of patient OTT interval and should order the presentation of therapies according to the classification of patients/proxies. Individualized decision making (IDM) might be an optimal strategy to increase the selection of thrombolysis, which providing important reference points for IDM in other clinical domains.